Framing Deaths, Embracing Lives: Alan M. Clark’s Jack the Ripper Victims Series - Lucyna Krawczyk-Żywko (Humanities)
Jack the Ripper fictions tend to be realist in mode, making frequent use of the Victorian press and archives to depict the 1888 murders. At the same time, they marginalise and exploit the victims, defining them as silent testimonies to the power of the elusive perpetrator. In contrast, Alan M. Clark’s Jack the Ripper Victims Series (2011–2018), consisting of five novels devoted to one canonical victim each, shifts the focus and depicts their lives. This article outlines the way the fictionalisations of the five women’s lives bring to the fore five other ‘crimes’ or transgressions: addiction, domestic violence, unemployment, sex work, and homelessness, but also the way these texts replace what is sensational and formulaic in Ripperature with something more than mundane and gritty in the lived experience of everyday people, such as moments of personal joy or professional accomplishments. Drawing on Kate Mitchell’s approach to history, cultural memory, and neo-Victorian fiction, it argues that pre-dating the publication of The Five (2019), Clark managed to realistically re-present (make present) and represent (create a portrayal of) the late-Victorian crime of dismissing the women who were murdered.